Alternative narratives of mythological storytelling: mythological parallels of different cultures revealed through the artifacts of the Archaeological Museum of Messenia and the use of AI tools - Κούβελα, Δήμητρα (Πανεπιστήμιο Πελοποννήσου, 2025)
This thesis explores the alternative narratives within museum exhibitions and particularly alternative narratives based on the mythological background of the artifacts, combined with the use of AI tools. In modern museums, alternative narratives offer visitors diverse perspectives of present knowledge from multiple viewpoints, usually raising awareness about social issues. An alternative narrative focusing on mythological storytelling was selected to connect certain artifacts of the exhibition of the Archaeological Museum of Messenia in Kalamata in order to highlight, through the narratives, the mythological similarities and parallels among distant civilizations that had no contact with one another. By studying three distinct mythologies—Aboriginal, Inuit, and Incan—and creating alternative narratives based on the mythological background of the artifacts, the research draws parallels with these cultures. It is highlighted that human nature is the same, beyond time and place. AI tools were used to contribute in creating the alternative narratives of the artifacts. Specifically, ChatGPT and Gemini were used to generate emotionally engaging texts for the museum artifact descriptions, based on mythological information supplied by the author. The use of AI tools emphasizes their importance in enhancing curatorial storytelling within museum contexts. Also, the mythological parallels contribute to a deeper understanding of universal human experiences.
Keywords: Αρχαιολογικό Μουσείο Μεσσηνίας (Καλαμάτα, Ελλάδα); Μουσειακές εκθέσεις -- Τεχνολογικές καινοτομίες -- Περιπτωσιολογικές μελέτες; Ψηφιακή αφήγηση -- Περιπτωσιολογικές μελέτες; Τεχνικές μουσείων -- Τεχνολογικές καινοτομίες -- Περιπτωσιολογικές μελέτες; Τεχνητή νοημοσύνη -- Πολιτιστικές εφαρμογές -- Περιπτωσιολογικές μελέτες; Μουσεία -- Τεχνολογία της πληροφορίας -- Περιπτωσιολογικές μελέτες; Τέχνη και μυθολογία -- Εκθέσεις -- Περιπτωσιολογικές μελέτες; Μυθολογία στην τέχνη -- Περιπτωσιολογικές μελέτες; Alternative narratives; AI tools; Mythological parallels; Εναλλακτικές αφηγήσεις; Εργαλεία τεχνητής νοημοσύνης; Μυθολογικά παράλληλα